1982
DOI: 10.1111/j.2044-8260.1982.tb00558.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of self‐induced vomiting in a multiply handicapped girl by ‘lemon juice therapy’ and concomitant changes in social behaviour

Abstract: Lemon juice contingently dispensed following self‐induced vomiting was found to effectively suppress this behaviour in a profoundly retarded multiply handicapped child. The programme was carried out by a teacher in the Special Care class of an ESN(S) school.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The first reported alternative to shock was contingent use of lemon juice upon the demonstration of pre-rumination behaviors described as ''vigorous tongue movements'' (Sajwaj et al, 1974). Several studies since that time have demonstrated the efficacy of this method both with ''normal'' infants, and mentally retarded adolescents and adults (Becker, Turner, & Sajwaj, 1978;Hogg, 1982;Marholin, Luiselli, Robinson, & Lott, 1980). Although these techniques produced significant and beneficial results (Demchak & Halle, 1985), concern was raised whether such practices produced negative side effects or were ethical and humane treatments for these individuals (Mayhew & Harris, 1978;Rollings, Baumeister, & Baumeister, 1977).…”
Section: Introductionmentioning
confidence: 98%
“…The first reported alternative to shock was contingent use of lemon juice upon the demonstration of pre-rumination behaviors described as ''vigorous tongue movements'' (Sajwaj et al, 1974). Several studies since that time have demonstrated the efficacy of this method both with ''normal'' infants, and mentally retarded adolescents and adults (Becker, Turner, & Sajwaj, 1978;Hogg, 1982;Marholin, Luiselli, Robinson, & Lott, 1980). Although these techniques produced significant and beneficial results (Demchak & Halle, 1985), concern was raised whether such practices produced negative side effects or were ethical and humane treatments for these individuals (Mayhew & Harris, 1978;Rollings, Baumeister, & Baumeister, 1977).…”
Section: Introductionmentioning
confidence: 98%